Endangered and threatened rush plants in Żuławy Wiślane (northern Poland) - Afranowicz, Renata (Biodiversity: Research and Conservation, 2006)
The paper presents results of the research concerning endangered and threatened rush species such as: Alisma gramineum, A. lanceolatum, Carex disticha, Hippuris vulgaris, Rumex aquaticus and Stellaria crassifolia. The aim of this study was to recognise distribution and to evaluate resources and contemporary state of this plant group in Żuławy Wiślane. The distribution is based on the published historical and present data from the last 130 years and on the results of field works in 2001-2005 years. The evaluation of nature resources, based on the distribution of valuable species, shows that Druzno lake is a distinguishable part of Żuławy Wiślane. For many years that area has been the place of concentration of several rare and endangered species populations.